The ambassador's daughter - Jenoff, Pam (Harlequin MIRA, 2013)
"Paris, 1919. The world's leaders have gathered to rebuild from the ashes of the Great War. But for one woman, the City of Light harbors dark secrets and dangerous liaisons, for which many could pay dearly. Brought to the peace conference by her father, a German diplomat, Margot Rosenthal initially resents being trapped in the congested French capital, where she is still looked upon as the enemy. But as she contemplates returning to Berlin and a life with Stefan, the wounded fiancé she hardly knows anymore, she decides that being in Paris is not so bad after all. Bored and torn between duty and the desire to be free, Margot strikes up unlikely alliances: with Krysia, an accomplished musician with radical acquaintances and a secret to protect; and with Georg, the handsome, damaged naval officer who gives Margot a job--and also a reason to question everything she thought she knew about where her true loyalties should lie. Against the backdrop of one of the most significant events of the century, a delicate web of lies obscures the line between the casualties of war and of the heart, making trust a luxury that no one can afford."--Page 4 of cover.